Social Challenges for Families in Teaching of the Latin American Bishops (CELAM) - Hajduk, Ryszard (Studia Warmińskie, 2022)
According to the teaching of the Second Vatican Council, the task of the Catholic Church is to observe the processes taking place in people’s lives and to read God’s plans in them, and, through events in the world, appeal to believers to take appropriate actions. The purpose of analyzing the final documents of the general conferences of Latin American bishops (CELAM) meeting Medellín (1968), Puebla (1979), Santo Domingo (1992) and Aparecida (2007) is to present their specific, i.e. pastoral theological approach to the situation of families in South and Central American countries. Taking into account sociological data, the Latin American bishops indicate the opportunities and threats which the modern family has to face. They do not forget that Catholic families are called to actively participate in shaping social life and to serve for the formation of mature personal attitudes of their members. Their particular task is to spread Gospel values in the world. Their implementation allows people to achieve the fullness of humanity. Thus, Latin American bishops show how to read the signs of the times and respond to them in the practice of Christian life.